Improving the Learning Outcomes and Motivation of Junior High School Students Through the Problem Based Learning Model Asissted by Animated Video Media on the Material of Two Variable Linear Equation Systems - Oktaviana, Dwi; Meilania, Desinca; Suryani, Lilis; Thomas, Thomas; Heri, Vinsensius (STKIP Singkawang, 2025)
This study aims to describe the Problem Based Learning (PBL) model assisted by animated videos in improving learning outcomes and learning motivation of class VIII students of SMP Negeri 19 Pontianak City on the material of Two Variable Linear Equation Systems (SPLDV). This study was conducted using a classroom action approach. The subjects in this study were all students in class VIII B of SMP Negeri 19 Pontianak City totalling 30 students. Data were obtained through students test results and questionnaires at the pre-cycle, cycle I and cycle II stages. The results showed that there was an increase in learning outcomes and student learning motivation on SPLDV material through the PBL learning model assisted by animated video media. This is evident from the average score obtained by students in the pre-cycle was 61.5 with 43.33% completeness, then in cycle I the score rose to 76.5 with 76.67% completeness and in cycle II the average student score increased to 84.17 with 90% completeness. Apart from that, student learning motivation in the pre-cycle category was 6.25% low, 56.25% medium, and 37.5% high, then in the first cycle it was 25% medium, 18.75% high and 56.25% very high, and in the second cycle it increased to 12.5% high and 87.5% very high. These results can be seen from cycle to cycle experiencing an increase in learning outcomes and motivation and have been able to spur students to be more active especially in learning on SPLDV material with PBL learning assisted by animated video media.Peningkatan Hasil dan Motivasi Belajar Siswa SMP Melalui Model Problem Based Learning Berbantuan Media Video Animasi Pada Materi Sistem Persamaan Linear Dua VariabelABSTRAKPenelitian ini bertujuan untuk mendeskripsikan model Problem Based Learning (PBL) berbantuan video animasi dalam meningkatkan hasil belajar dan motivasi belajar siswa kelas VIII SMP Negeri 19 Kota Pontianak pada materi Sistem Persamaan Linear Dua Variabel (SPLDV). Penelitian ini dilakukan dengan menggunakan pendekatan tindakan kelas. Subjek dalam penelitian ini adalah seluruh peserta didik di kelas VIII B SMP Negeri 19 Kota Pontianak yang berjumlah 30 siswa. Data diperoleh melalui hasil tes dan angket siswa pada tahap pra siklus, siklus I, dan siklus II. Hasil penelitian menunjukan bahwa adanya peningkatan hasil belajar dan motivasi belajar siswa pada materi SPLDV melalui model pembelajaran PBL berbantuan media video animasi. Hal ini terbukti dari nilai rata-rata yang diperoleh siswa pada pra siklus adalah 61,5 dengan ketuntasan 43,33% kemudian pada siklus I nilainya naik menjadi 76,5 dengan ketuntasan 76,67% dan pada siklus II rata-rata nilai siswa meningkat menjadi 84,17 dengan ketuntasan 90%. Selain itu, motivasi belajar siswa pada pra siklus dengan kategori rendah sebanyak 6,25%, sedang sebanyak 56,25%, dan tinggi sebanyak 37,5% kemudian pada siklus I dengan kategori sedang 25%, tinggi 18,75%, dan sangat tinggi 56,25% dan siklus II meningkat menjadi kategori tinggi 12,5% dan sangat tinggi 87,5%. Hasil tersebut dapat dilihat dari siklus ke siklus mengalami peningkatan hasil dan motivasi belajar dan telah mampu memacu para siswa untuk lebih aktif khususnya dalam pembelajaran pada materi SPLDV dengan pembelajaran PBL berbantuan media video animasi.Kata Kunci :hasil belajar; motivasi belajar; media video pembelajaran; SPLDV